Ferroelectricity and Crystal Phases in Mixed‐Cation Lead Iodide Perovskite Solar Cells. Issue 12 (13th October 2022) - Schulz, Alexander Deniz; Schmitt, Max Oliver; Braun, Moritz; Colsmann, Alexander; Hinterstein, Manuel; Röhm, Holger
Abstract : After the discovery of ferroelectricity in archetypal methylammonium lead iodide (MAPbI3 ), the discussion arose, if more advanced derivatives thereof are also ferroelectric and to what extent the polar domains mitigate detrimental charge carrier recombination in perovskite solar cells. Herein, the A‐site cation methylammonium is gradually substituted with formamidinium and cesium. The domain contrast measured by piezoresponse force microscopy is correlated with the distortion of the crystal structure measured by X‐ray diffraction. By Rietveld analysis, a detailed structural model together with texture information is determinded, which reveals an intriguing interplay between lead iodide and the perovskite phases. Finally, the bearing of ferroelectric domains in mixed‐cation perovskites on the solar cell performance is discussed. Abstract : By employing X‐ray diffraction and piezoresponse force microscopy, a ferroelectric to nonferroelectric phase transition at room temperature when methylammonium is partially substituted by formamidinium and cesium is revealed. The structural study is correlated with solar cells around this phase transition to explore the impact of the microstructure on energy conversion.